PiezoGRIN: A High-Pressure Chamber Incorporating GRIN Lenses for High-Resolution 3D-Microscopy of living Cells and Tissues - Schneidereit, Dominik; Schürmann, Sebastian; Friedrich, Oliver (Advanced Science, 2018)
A high‐pressure optical chamber, PiezoGRIN, that facilitates label‐free 3D high‐resolution live‐cell multiphoton microscopy in thick tissue samples is presented. A set of two Gradient Index (GRIN) rod lenses is integrated into the chamber as an optical guide and allows for the adjustment of the focal plane through the sample providing a field of view volume of 450 × 450 × 500 µm (x, y, z). An optical lateral resolution of 0.8 µm is achieved by using two‐photon excitation with 150 fs pulses of a 810 nm titanium–sapphire laser at hydrostatic pressures up to 200 MPa. With the PiezoGRIN setup, it is possible to follow pressure‐induced changes in subcellular structure of unstained vital mouse skeletal muscle tissue up to 200 µm below the tissue surface.<br
Keywords: second harmonic generation; skeletal muscle; high pressure; multiphoton microscopy